Strength characterisation of shale using Mohr-Coulomb and Hoek-Brown criteria - Mohd. Fauzi, Nurihan (2015)
Strength parameters of rock material are usually determined from laboratory test on intact rock samples. Uncertainties arise in predicting the behaviour of a rock mass under confinement due to the presence of discontinuous. Compared with the intact rock, discontinuity such as joint induces inhomogeneous and anisotropic behaviour in the rock mass. Several empirical approach such as Rock Mass Rating (RMR) is available to classify and evaluate the strength of rock mass. However, the RMR method is not suitable to be applied for the very poor quality of rock such as shale, due to its limitation. This study attempts to verify the strength parameters of intact rock using Hoek-Brown (H-B) and Mohr-Coulomb (M-C) failure criterion. The RocData software is utilised to evaluate and assess the strength parameter of the shale. Result obtained indicates that H-B criterion, which describe a non-linear increase of strength compared to M-C. Hence, H-B criterion shows better presentation of shale under field condition in comparison to M-C method.